Visible Results, Invisible Factors: Impact of Socio-economic Factors on Improving English Language Achievement in Sri Lankan Schools - Dr MASP Manchanayaka; Dr H Palihakkara; Dr S Fernando; TB Jeganathan (Journal of Studies in Education, 2024)
This paper presents the findings of a study that investigated the nexus between the parental level of education and the level of the English language achievement at the Ordinary Level (O/Level) Examination. Determining how socio-economic factors affect the achievement level of English, exploring what socio-economic factors affect the achievement of the English language, and identifying the primary socio-economic factors were the objectives. A non-experimental cross-sectional research design was used in conducting the study. The sample consisted of 291 volunteer participants from six schools in the western province. We administered a research-team designed Likert scale type questionnaire to gather the data. The instrument was pilot-tested with 74 participants. In a statistical approach to data analysis, a regression analysis was run in SPSS (version 26). Findings showed that the English language proficiency of the participants increased by 0.691 for each education level of the father, and it was increased by 0.789 for each education level of the mother. Equitable teaching of the English language, availing more time and classwork to improve the achievement levels of the English language, and using quality inputs to give more support to the students who receive lower grades were suggested as part of recommendations.